Strategi Guru SKI Dalam Mengatasi Keterbatasan Sumber Belajar Untuk Meningkatkan Pemahaman Belajar Siswa Di MIS Al Washliyah Desa Bangun Sari Baru Tanjung Morawa Deli Serdang - Khairunnisa, Dwi; Nasution , Hasnil Aida; Hidayah , Nurul (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to describe the strategies implemented by Islamic Cultural History (SKI) teachers at MIS Al Washliyah, Bangun Sari Baru Village, in overcoming the challenges of limited learning resources. In many rural educational settings, the scarcity of textbooks and instructional media often hinders the achievement of comprehensive student understanding. This study employs a qualitative descriptive approach, with data collection techniques including in-depth interviews, participatory observation, and documentation. The findings reveal that teachers navigate these constraints through a